Spatial and seasonal variations of organic carbon distributions in typical intertidal sediments of China. (April 2020) - Zhang, Yushuang; Xiao, Xiaotong; Liu, Dongyan; Wang, Enhui; Liu, Ke; Ding, Yang; Yao, Peng; Zhao, Meixun
Highlights: Intertidal sediment OC contents increased with decreasing sediment grain size. OC contents were higher in wet season than dry season mainly due to higher inputs. Terrestrial OC contributions were higher in large estuaries than small estuaries. Intertidal sediment carbon stocks were comparable to those in shelf sediments. Abstract: Intertidal zones are the main sites for land-ocean interaction and play an important role in transporting and accumulating organic carbon (OC). Understanding sources and preservation of sedimentary OC are vital to better evaluate the processes controlling the OC distribution in intertidal zones. In this study, we present bulk parameters of total organic carbon (TOC), δ 13 Corg, grain size and biomarker contents in surface sediments of 14 typical intertidal zones along China's coastline during both the wet season (WS) and the dry season (DS). Statistical analysis of our data set showed that TOC and biomarker contents were generally high in small estuaries, intermediate but more variable in large estuaries and low in non-estuaries; and these distribution patterns broadly correlated with sedimentary clay contents. TOC and biomarker contents were generally higher in the WS than the DS reflecting both OC inputs and preservation. A binary mixing model based on δ 13 Corg and biomarker proxies revealed that large estuaries were characterized by higher terrestrial OC fractions (62–80%) except for the Yellow River Estuary (24%), while lower terrestrial OC fractions occurred in non-estuaries (13–15%). Variable OC contributions were found in small estuaries, with most sites characterized by low terrestrial OC contributions (3–35%), but high terrestrial OC contributions were found at the Qiantang River Estuary site (59%) and the Jiulong River Estuary site (67%). Carbon stocks in Chinese intertidal sediments are comparable with those in marine sediments from shelf areas and the Exclusive Economic Zone (EEZ). This study suggests that intertidal sediments are potentially an important carbon sink.